2012
DOI: 10.1038/ejcn.2012.111
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of folate status in pregnant women: results from a national cross-sectional survey in Belgium

Abstract: BACKGROUND/OBJECTIVES: Folic acid deficiency during pregnancy can lead to neural tube defects (NTD) in the fetus. Folate status was determined in a representative sample of Belgian pregnant women and determinants of folate status were assessed. SUBJECTS/METHODS: The women were selected using a multi-stage proportionate-to-size sampling design. Blood samples were collected and a questionnaire was completed face-to-face with a study nurse. Erythrocyte (red blood cell (RBC)) folate concentration was measured by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
0
17
2
2
Order By: Relevance
“…Of the remaining 95 papers, 63 were excluded on the basis of the full text. The remaining 32 articles are included in this review, as shown in Supplemental S1 (Adaikalakoteswari et al, ; Ambroszkiewicz, Chelchowska, Lewandowski, Gajewska, & Laskowska‐Klita, ; Baker et al, ; Bakker et al, ; Bergen et al, ; Bodnar et al, ; Coker et al, ; Dayaldasani et al, ; Frery et al, ; D. Furness et al, ; D. L. Furness, Yasin, Dekker, Thompson, & Roberts, ; Gadowsky et al, ; Hay et al, ; Jauniaux, Johns, Gulbis, Spasic‐Boskovic, & Burton, ; Knight et al, ; Knudtson et al, ; Larroque et al, ; Matsuzaki et al, ; McDonald, Perkins, Jodouin, & Walker, ; Mito et al, ; Nilsen et al, ; Ozerol, Ozerol, Gokdeniz, Temel, & Akyol, ; Pagan, Hou, Goldenberg, Cliver, & Tamura, ; Prasodjo et al, ; Relton et al, ; Sram, Binkova, Lnenickova, Solansky, & Dejmek, ; Stark et al, ; Stark, Pawlosky, Sokol, Hannigan, & Salem Jr., ; Van Uitert et al, ; van Wersch, Janssens, & Zandvoort, ; Vandevijvere, Amsalkhir, Van Oyen, & Moreno‐Reyes, ; Yila et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining 95 papers, 63 were excluded on the basis of the full text. The remaining 32 articles are included in this review, as shown in Supplemental S1 (Adaikalakoteswari et al, ; Ambroszkiewicz, Chelchowska, Lewandowski, Gajewska, & Laskowska‐Klita, ; Baker et al, ; Bakker et al, ; Bergen et al, ; Bodnar et al, ; Coker et al, ; Dayaldasani et al, ; Frery et al, ; D. Furness et al, ; D. L. Furness, Yasin, Dekker, Thompson, & Roberts, ; Gadowsky et al, ; Hay et al, ; Jauniaux, Johns, Gulbis, Spasic‐Boskovic, & Burton, ; Knight et al, ; Knudtson et al, ; Larroque et al, ; Matsuzaki et al, ; McDonald, Perkins, Jodouin, & Walker, ; Mito et al, ; Nilsen et al, ; Ozerol, Ozerol, Gokdeniz, Temel, & Akyol, ; Pagan, Hou, Goldenberg, Cliver, & Tamura, ; Prasodjo et al, ; Relton et al, ; Sram, Binkova, Lnenickova, Solansky, & Dejmek, ; Stark et al, ; Stark, Pawlosky, Sokol, Hannigan, & Salem Jr., ; Van Uitert et al, ; van Wersch, Janssens, & Zandvoort, ; Vandevijvere, Amsalkhir, Van Oyen, & Moreno‐Reyes, ; Yila et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Table shows the results of the 28 studies measuring levels of folate or its metabolites in a total of 30,938 participants (Adaikalakoteswari et al, ; Ambroszkiewicz et al, ; Baker et al, ; Bergen et al, ; Bodnar et al, ; Coker et al, ; D. Furness et al, ; D. L. Furness et al, ; Gadowsky et al, ; Hay et al, ; Jauniaux et al, ; Knight et al, ; Larroque et al, ; Matsuzaki et al, ; McDonald et al, ; Mito et al, ; Nilsen et al, ; Ozerol et al, ; Pagan et al, ; Prasodjo et al, ; Relton et al, ; Sram et al, ; Stark et al, ; Stark et al, ; Van Uitert et al, ; van Wersch et al, ; Vandevijvere et al, ; Yila et al, ). Twenty‐six studies measured folate levels in maternal blood (serum, plasma, or erythrocytes) and seven studies measured folate levels in umbilical cord blood.…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organization recommends supplementation with folic acid before conception until the 12 th week of pregnancy [24]. The authors have shown that 39% of pregnant women from Belgium do not have adequate level of folate in the first trimester to prevent neural tube defects [25]. Out of them, 59.9% of women continue to take supplements containing folic acid throughout gestation [12].…”
Section: Role Of Folate In Organismmentioning
confidence: 99%
“…Studies have shown that women who are aware of the importance of folic acid before their pregnancy are more likely to use folic acid supplements. All these women have been shown to have an inadequate folate status during pregnancy, inadequate intake of foods rich in folate, enriched foods or folic acid supplements [22,25,41,45,51,53]. In addition, women who happen to be single during their pregnancy or those with unplanned pregnancy should be encompassed as well [25].…”
Section: Folic Acid Supplements and Food Fortificationmentioning
confidence: 99%
“…С другой стороны, по данным проведенных за последние десятилетия исследо-ваний [24], отмечено, что развитие ДНТ связано с авита-минозом, а экзогенное или периконцепционное посту-пление ФК в организм будущей матери способствует сни-жению риска ДНТ у плода. Необходимо отметить, что не только дефицит фолатов в организме беременной являет-ся фактором риска развития ДНТ, но и особенность тече-ния всего процесса метилирования влияет на формирова-ние ДНТ [20,25]. В ряде исследований [26] сообщается о профилактике ДНТ и коррекции дефектов биосинтеза при поступлении экзогенной ФК и тимидина у гомози-готных эмбрионов мыши splotch (Pax3).…”
unclassified